Addressing artifacts of colorimetric anticancer assays for plant-based drug development - Batool, Salma; Javaid, Seejal; Javed, Hira; Asim, Laiba; Shahid, Izzah; Khan, Mishal; Muhammad, Amna (Medical oncology, 2022)
Cancer has become the silent killer in less-developed countries and the most significant cause of morbidity worldwide. The accessible and frequently used treatments include surgery, radiotherapy, chemotherapy, and immunotherapy. Chemotherapeutic drugs traditionally involve using plant-based medications either in the form of isolated compounds or as scaffolds for synthetic drugs. To launch a drug in the market, it has to pass through several intricate steps. The multidrug resistance in cancers calls for novel drug discovery and development. Every year anticancer potential of several plant-based compounds and extracts is reported but only a few advances to clinical trials. The false-positive or negative results impact the progress of the cell-based anticancer assays. There are several cell-based assays but the widely used include MTT, MTS, and XTT. In this article, we have discussed various pitfalls and workable solutions.